Answer:
see explanation
Step-by-step explanation:
Given that x = - [tex]\frac{4}{5}[/tex] is a solution of the equation
Then substitute this value into the equation and solve for b
10 ( - [tex]\frac{4}{5}[/tex] )² + b(- [tex]\frac{4}{5}[/tex] ) - 3 = 0
10 × [tex]\frac{16}{25}[/tex] - [tex]\frac{4}{5}[/tex] b - 3 = 0
[tex]\frac{32}{5}[/tex] - [tex]\frac{4}{5}[/tex] b - 3 = 0
Multiply through by 5
32 - 4b - 15 = 0
17 - 4b = 0 ( subtract 17 from both sides )
- 4b = - 17 ( divide both sides by - 4 )
b = [tex]\frac{17}{4}[/tex] ← value of b
Given α and β are the roots of a quadratic equation, then
α + β = - [tex]\frac{b}{a}[/tex]
let α = - [tex]\frac{4}{5}[/tex], then with a = 10 and b = b
- [tex]\frac{4}{5}[/tex] + β = - [tex]\frac{\frac{17}{4} }{10}[/tex] = - [tex]\frac{17}{40}[/tex]
β = - [tex]\frac{17}{40}[/tex] + [tex]\frac{4}{5}[/tex] = [tex]\frac{3}{8}[/tex]
Hence the other solution is x = [tex]\frac{3}{8}[/tex]